Effect of Salinity on Survival and Growth of Macrobrachium Rosenbergii (De Man) - Venugopalan I K (Department of Aquaculture, College of Fisheries, 1988)
The effect of salinity on survival and growth of macrobrachium rosenbergii (De Man) was studied with a view to establish the optimum salinity conditions under which it can be cultured. The effect of salinity on survival was assessed by conducting short-term tolerance studies wherein the effect of abrupt transfer and gradual acclimation to the test salinity levels of 5,10,15,20,25,26.5,28.5,30 and 35 ppt was separately studied. In both abrupt transfer and gradual acclimation, no mortality was observed upto 25 ppt within a period of 120 hrs. The LC50 values for 72 hr and 120 hr were 33.3 ppt and 31.6 ppt for gradual acclimation and 29.85 ppt and 28.18 ppt for abrupt transfer respectively. Acclimation prolonged the survival time of the juvenile in the test salinity levels.